Arabidopsis thaliana Hcc1 is a Sco-like metallochaperone for Cu A assembly in Cytochrome c Oxidase - Llases, María Eugenia (2019)
The assembly of the CuA site in Cytochrome c Oxidase (COX) is a critical step for aerobic respiration in COX-dependent organisms. Several gene products have been associated with the assembly of this copper site, the most conserved of them belonging to the Sco family of proteins, which have been shown to perform different roles in different organisms. Plants express two orthologs of Sco proteins: Hcc1 and Hcc2. Hcc1 is known to be essential for plant development and for COX maturation, but its precise function has not been addressed until now. Here, we report the biochemical, structural and functional characterization of Arabidopsis thaliana Hcc1 protein (here renamed Sco1). We solved the crystal structure of the Cu+1-bound soluble domain of this protein, revealing a tri coordinated environment involving a CxxxCxnH motif. We show that AtSco1 is able to work as a copper metallochaperone, inserting two Cu+1 ions into the CuA site in a model of CoxII. We also show that AtSco1 does not act as a thiol-disulfide oxido-reductase. Overall, this information sheds new light on the biochemistry of Sco proteins, highlighting the diversity of functions among them despite their high structural similarities.